Combination Therapy of Statins with Ezetimibe - Moriguchi, Emilio H.; Vieira, Jose Luiz d. C. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
Ezetimibe is a cholesterol absorption inhibitors that blocks the intestinal absorption of cholesterol and biliary cholesterol without affecting the uptake of triglyceride or fat-soluble vitamins. The co-administration of ezetimibe with statin has been shown to produce significant incremental reduction in LDL-C beyond that achieved with statin therapy alone. The efficacy and safety of this strategy has been studied in a several trials in a great number of patients. The mean difference between treatments significantly favoured the ezetimibe/statin combination over placebo/statin for total cholesterol (p < 0.0001), LDL-C (p < 0.0001) and HDL-C (p < 0.0001). The probability of reaching the LDL-C treatment goal was significantly higher for patients on ezetimibe/statin relative to those on placebo/ statin (p < 0.0001). Elevations in creatine kinase, alanine aminotransferase or aspartate aminotransferase that were considered as an adverse effect did not differ significantly between treatments. Ezetimibe co-administered with ongoing statin therapy provides significant additional lipid-lowering in patients not at LDL-C goal on statin therapy alone, allowing more patients to reach their LDL-C goal with no increment in the side-effects.
Keywords: LDL